Antibody responses to invariant antigens of Trypanosoma congolense - Authié, Edith; Boulange, A.F.; Muteti, D.; Taylor, K.A.; Williams, D.J.L. (International Laboratory for Research on Animal Diseases, 1994)
Trypanotolerance involves an ability to both control trypanosome multiplication and resist the pathogenic effects of trypanosome infection. Studies in the African Trypanotolerant Livestock Network and elsewhere have shown that the latter capacity is more closely correlated than the former to the resistance of individual taurine cattle, as assessed by their survival and productivity under natural field challenge. The trypanosome molecules that trigger the disease have not been studied. We have hypothesized that some of the pathogenic factors are invariant; i.e. non-VSG (variant suface glycoprotein) anvariant; i.e. non-VSG (variant surface glycoprotein) antigens, and that a more efficient control of the disease might operate in trypanotolerant cattle through a more efficient immune response to these antigens. It is analysed that the pattern of serological responsiveness in N'Dama (trypanotolerant) and Boran cattle (trypanosusceptible) during a reinfection with T. congolense, using the Western blot technique. Sera from infected cattle reacted with three major antigens. Two of these antigens, with molecular masses of 69 and 33 kDa were differentially recognized by the immune system of the two breeds.